Reinforced dowel type connections: mechanical behaviour under cyclic tests - Rodrigues, Leonardo Filipe Guilherme (2021)
Dowel type joints are widely used in timber structures given their ease of construction and ability to dissipate energy when subjected to cyclic loading. The behaviour of these connections under cyclic loading depends on good detailing at the design phase, which is developed to guarantee ductile failure modes and avoid wood splitting through careful consideration of the dowel-to-edge and dowel-to-end distances. This conference paper presents the cyclic response of a dowel type connection that is reinforced with self-tapping screws (STS). The experimental campaign included unreinforced joints, with inadequate and adequate end distances as defined per Eurocode 5, and joints with self-tapping screws fastened perpendicular to the dowels to avoid premature splitting. To reduce the number of variables of the experimental design, dowel slenderness and position of the reinforcements were kept throughout the testing programme. Moreover, the laboratory tests only considered specimens loaded in the parallel-to-grain direction. The influence of timber species was evaluated by using specimens from Pinus pinaster and Pinus sylvestris. Laboratory testing results highlight the ability of dowel-type joints to withstand large displacement reversals without rupture. The reinforcement scheme proposed in this work achieved ductility values consistent with the Eurocode's Ductility Class High structures.